Teleodynamics and institutional change: The hardship of protecting the Amur tiger, big-leaf mahogany, and gray wolf - Hiedanpää, Juha; Salo, Matti; Kotilainen, Juha
The global biodiversity is in decline because modern societies are organized for that purpose. The design, implementation and enforcement of international, regional and national environmental policies have not helped to reverse the trend. In our paper, we analyze the hardship of protecting the gray wolf in Finland, the big-leaf mahogany in Peru, and the Amur tiger in Russia. Our comparative approach is based on the old institutional economics, and our key concept - the unit of analysis - is a transaction, i.e. enactment, practice and transfer of formal and informal rights to future benefits. Transactions challenge, disturb and re-organize the existing institutional scaffold. William Connolly (The Fragility of Things, 2013) and Terrence Deacon (Incomplete Nature, 2012) have recently argued that teleodynamics, the purposeful and end-directed behaviors and the reactions and disturbances in other related ententional behaviors are key to understand not only the dynamics of institutional change per se but also, and especially so, the emergent patterns of behavior resulting from resistance and adaptation. These teleodynamic consequences reveal the problems in institutional fit, i.e. how the institutional arrangements, particular customary circumstances and habitual actors fit together. We abduct three types of emerging order springing from the reactions to national biodiversity policies: (i) the practice of faking the institutional fit, (ii) the practice of disobedience; and, (iii) willingness to take part in the making of new institutional arrangements. These vary according to the purpose, working rules (set of rights) and motivation. We explain the interrelated meaning of purpose, working rules and motivation in the context of institutional fit in detail. In our cases, the fit is not exactly the one envisioned through the authoritative rules and the purpose of institutional conservation, but it is an order nevertheless, and that order is not necessarily good for endangered species. 2015